Konsep Pedagogik dalam Pandangan Imam Al-Zarnuzi - Choiri, Moh. Miftahul (Discovery, 2024)
Pedagogical concepts are important in learning. Successful learning can be  ensured that there is good communication or interaction between the teacher and students. Humanism learning or what is better known as learning that humanizes students is that it emphasizes a fun learning process. a learning process that can understand the potential and characteristics of students. learning that can develop students' talents and interests. This research will explore the pedagogical concept in Imam Al-Zarnuzi's view in the learning process. The ultimate goal is for learning to be carried out optimally.The research method used is primary and secondary data documentation methods. It is hoped that this research will be useful for all communities, schools and especially researchers themselves.